Tingkat Kebugaran Jasmani Siswa Kelas V SDN Tawangmas 01, SDN Tanjung Mas dan SDN Sekaran 01 Masa New Normal Tahun 2022 - Putri Pamuji, Hernika Isnaeni; Setiawan, Ipang (Indonesian Journal for Physical Education and Sport, 2023)
The Covid-19 pandemic has forced learning to be done online, including physical education learning. The purpose of this study was to determine the level of physical fitness of the fifth grade elementary school students. The research method used is descriptive quantitative survey method. The population in this study were fifth grade students of SD Negeri Tawangmas 01, SD Negeri Tanjung Mas and SD Negeri Sekaran 01 with total sampling using a total sample of 102 students. The instrument uses TKJI aged 10-12 years. The data analysis technique used descriptive quantitative with percentages. The results of this study are the physical fitness level of fifth grade students at SD Negeri Tawangmas 01 in the medium category (80%), the physical fitness level in the fifth grade students at SD Negeri Tanjung Mas in the medium category (58.62%), the physical fitness level in the fifth grade students at SD Negeri Sekaran. 01 good category (44.74%). The conclusion of this research is the level of physical fitness of the fifth grade students of SD Negeri Tawangmas 01, SD Negeri Tanjung Mas and SD Negeri Sekaran 01 in the medium category (58.82%). The author's suggestions for research 1) For students, they should maintain a healthy lifestyle and fulfill balanced nutrition in order to improve their physical fitness. 2) Teachers should always control the level of physical fitness of their students. 3) Parents always control their children's living habits at home.